2014
DOI: 10.1088/1367-2630/16/10/105018
|View full text |Cite
|
Sign up to set email alerts
|

Strain driven topological phase transitions in atomically thin films of group IV and V elements in the honeycomb structures

Abstract: We have investigated topological electronic properties of freestanding bilayers of group IV (C, Si, Ge, Sn, and, Pb) and V (As, Sb, and, Bi) elements of the periodic table in the buckled and planar honeycomb structures under isotropic strain using first-principles calculations. Our focus is on mapping strain driven phase diagrams and identifying topological phase transitions therein as a pathway for guiding search for suitable substrates to grow two-dimensional (2D) topological insulators (TIs) films. Bilayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 28 publications
(38 reference statements)
4
57
0
1
Order By: Relevance
“…In addition, although the low-buckled structure naturally breaks the mirror symmetry about the plane leading to an intrinsic Rashba-type spin-orbit coupling, this is not detrimental to the 2D Z 2 TIs since the intrinsic Rashba spin-orbit coupling is momentum-dependent and vanishes at the Dirac K/K ′ points [94]. Another striking property of the low-buckled structure is the external tunability when an electric field [95][96][97][98] or strain [99,100] is applied.…”
Section: Low-buckled Honeycomb Latticementioning
confidence: 99%
“…In addition, although the low-buckled structure naturally breaks the mirror symmetry about the plane leading to an intrinsic Rashba-type spin-orbit coupling, this is not detrimental to the 2D Z 2 TIs since the intrinsic Rashba spin-orbit coupling is momentum-dependent and vanishes at the Dirac K/K ′ points [94]. Another striking property of the low-buckled structure is the external tunability when an electric field [95][96][97][98] or strain [99,100] is applied.…”
Section: Low-buckled Honeycomb Latticementioning
confidence: 99%
“…Recent theoretical work has predicted that a number of organic compounds [9][10][11] as well as many atomically thin films of elements of groups IV and V as well III-V compounds assume a 2D-TI phase in the honeycomb structure. Beyond carbon [12], the predicted 2D-TIs include films of silicon, germanium [13], tin [14], and bismuth [15], and InBi, GaBi, and TlBi [16] alloys at their equilibrium honeycomb structures, while arsenic [17], antimony [18], BBi, and AlBi [16] transition to a 2D TI phase under strain. Several of the newly predicted 2D-TIs exhibit band gaps large enough to exceed thermal excitation energy at room temperature [15,16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…19 Ma et al also successfully predicted the large-bulk-gap topological phases in the methyl-functionalized Bi, Sb and Pb thin bilayer films. 34 Furthermore, Winterfeld et al demonstrated that HgSe can be tuned into a 3D topological insulator via proper strain engineering. For example, by applying a perpendicular electric field on few-layer black phosphorous, a normal-totopological phase transition in this multilayer stack of phosphorene can be achieved, in which the topological band inversion entirely originates from the electric-field-induced Stark effect, whereas the effect of SOC is to open a band gap at the Dirac-like band crossing, rendering the system a 2D TI.…”
Section: Introductionmentioning
confidence: 99%